(3EfHGg GdQhGI Ydi CfHGA GdfMGIs - (3Ydj Hf jhSa Hf EHQGgje GdTjHGfj GdbaWj, CHh GdMSf, LeGd GdOjf,J (B646 (3g` s
(3ChdgG (B:s
(3ajg MQa GdaGA hGdbGa hGdcGa hGddGe hGdeje MQa GdaG GdaVd Hf GdNHGf GHh NdjaI cGf CMO CUMGH GdMOjK s
(3BNQgG (B:s
(3hcGf efUakG hdg gfGc TgQI XGgQI aJfGaS Cgd GdCOH ai JMUjd eUfaGJg hjJRGMehf Ydi GOQGc ahGFOg s
(3PcQ Cf YdjgG JhbjY GdeDda ChSHWgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B263s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B559 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B35 s
Keywords: (3GdJGQjNs